Model Pendidikan Akhlak dalam Kitab Nashoihul Ibad Karya Syeikh Imam Nawawi Al-bantani - Sya’diyah, Siti Aminatus; Fauzi, Ahmad; Maghfiroh, Ummi Lailia (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The importance of developing moral education which includes holistic and sustainable aspects has highlighted attention to the moral education model. The book